Comparison of laboratory performance of surface treatments designed using the methodologies of TxDOT and Austroads - Herra Gómez, Luis Diego (2025)
Chip seals are an alternative to preserve the current condition of a road and to improve some of its characteristics such as impermeability and surface texture. Despite its benefits, there is currently no formally defined test method to evaluate the laboratory performance of chipseals elaborated from different materials or design methodologies. For this reason, in this article, based on a series of modifications made to the ASTM D7000 test, the performance of chipseals developed from the design methodologies adopted by the transportation agencies TxDOT and Austroads is compared. These methodologies start from the two most fundamental lines of thought for the design of asphaltic surface treatments, the Hanson principles, used in the Austroads method and the Kearby principles, used in the TxDOT method. From the tests carried out, it was determined that the Austroads methodology promotes chipseals that would have a greater amount ofremaining aggregate, after simulating the effects of vehicular traffic on the samples of asphaltic surface  treatments prepared, being an aspect that could positively influence their performance.